2015
DOI: 10.1136/thoraxjnl-2015-207245
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the efficacy and safety ofN-acetylcysteine in preventing aminoglycoside-induced ototoxicity: implications for the treatment of multidrug-resistant TB

Abstract: This review provides evidence for the safety and otoprotective effect of NAC when coadministered with aminoglycoside. It represents a strong justification for a clinical trial to investigate the effect of concomitant NAC treatment in patients receiving aminoglycosides as part of MDR-TB treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 64 publications
(32 reference statements)
0
40
0
3
Order By: Relevance
“…C‐terminally extended aberrant proteins produced as a result of gentamycin treatment are presented by MHC class I molecules, which may invoke autoimmune diseases . Therefore, understanding the quality control mechanism regulating 3′‐UTR translation would contribute to alleviating the side effects of aminoglycosides including ototoxicity and renal failure . Ataluren, formerly known as PTC124, is used for the treatment of Duchenne muscular dystrophy (DMD) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C‐terminally extended aberrant proteins produced as a result of gentamycin treatment are presented by MHC class I molecules, which may invoke autoimmune diseases . Therefore, understanding the quality control mechanism regulating 3′‐UTR translation would contribute to alleviating the side effects of aminoglycosides including ototoxicity and renal failure . Ataluren, formerly known as PTC124, is used for the treatment of Duchenne muscular dystrophy (DMD) .…”
Section: Resultsmentioning
confidence: 99%
“…The correlation coefficients (R) between the MKD and the RFP/GFP ratio of mutants are shown on the bottom right of the bar graph of the RFP/GFP ratio. regulating 3 0 -UTR translation would contribute to alleviating the side effects of aminoglycosides including ototoxicity and renal failure [48]. Ataluren, formerly known as PTC124, is used for the treatment of Duchenne muscular dystrophy (DMD) [49][50][51][52].…”
Section: Translation Arrest At the 3 0 -Utr Contributes To Downregulamentioning
confidence: 99%
“…In previous clinical studies, some side effects were observed after NAC treatment against aminoglycosideinduced ototoxicity for more than 6 weeks, such as abdominal pain, nausea, vomiting and diarrhea. [22][23][24] In the future studies, the toxic effects of NAC after longterm treatment should be further evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the efficacy of this dose is unclear, and the use of this dose is not currently recommended. Other possibilities include the coadministration of N-acetylcysteine or other antioxidants (23), genetic testing for mutations in the mitochondrial gene encoding 12S rRNA (MT-RNR1), and avoiding aminoglycosides in patients with these mutations (24)(25)(26), though the prevalence of these mutations is low.…”
Section: Discussionmentioning
confidence: 99%